Clinical characteristics, audiological and neurodevelopmental outcomes of newborns with congenital cytomegalovirus infection: This article was corrected and republished online on April 3, 2019. Please see Erratum (Swiss Med Wkly. 2019;149:w20075) (Swiss Medical Weekly, 2018)
BACKGROUND Congenital cytomegalovirus (cCMV) infections are the leading nongenetic cause of congenital sensorineural hearing loss (SNHL); however the true impact of cCMV infections remains unknown. AIMS OF THE STUDY (1) To identify the number of asymptomatic and symptomatic cCMV infections diagnosed between 1999 and 2014 at the Lausanne University Hospital; (2) to describe the audiological and neurodevelopmental outcomes of infants with cCMV infection; and (3) to compare clinical outcomes between infants born to mothers with primary versus nonprimary infection. METHODS This was a single-centre, observational, exploratory, retrospective study of newborns diagnosed with cCMV infection at the Lausanne University Hospital between 1999 and 2014. RESULTS Fifty newborns with cCMV infection were identified; 39 (78%) were symptomatic at birth, of whom 29 (74%) were neurologically symptomatic. Twelve children (24%) presented with subsequent abnormal audiological and/or neurodevelopmental outcomes. Newborns born to mothers with a nonprimary infection were more often symptomatic at birth than those born to mothers with a primary infection. CONCLUSIONS All infants with subsequent SNHL or abnormal neurodevelopment were symptomatic at birth. Similar long-term neurodevelopmental and audiological outcomes were observed in infants born to mothers with a primary and nonprimary infection.